The Effectiveness of Student Teams Achievement Division Cooperative Learning in Improving Mathematics Skills in VTE Engineering Students - Sarinah Ziziumiza; Jabaidah Bungsu; Masitah Shahrill (International Journal of Pedagogy and Teacher Education, 2022)
Student teams-achievement divisions (STAD) is a cooperative learning strategy in which small groups of learners with different abilities work together to achieve a shared goal. This study investigates the effectiveness of employing STAD amongst vocational and technical engineering (VTE) students. The objectives are to identify if using STAD in the classroom enhances students’ learning and improves their performance and attitude toward cooperative learning strategies, and also to identify their learning preferences with regard to studying individually or cooperatively. The study draws from quantitative data from pre- and post-tests, student attitude questionnaires, rubric evaluation and group achievement test to assess students’ performance in groups. A paired t-test was conducted, with the results demonstrating a significant difference between the students’ scores in the pre- and post-tests, indicating that STAD cooperative learning improved student performance in mathematics skills and the learning outcomes.